(untitled) (Biological Sciences - PJSIR, 2021)
This study describe the design features and performance of the unglazed transpired solar dryer for large and medium scale drying of Dates in the Dates growing area of Pakistan. The dryer has the designed capacity to dry 500 Kg of Dates from Khalaal (70% humidity) to Tamar (25% humidity), at 55 C ± 5 C in 72 continuous hours using biomass furnace as an auxiliary heat source and it covers approximately 256 m2 areas. This is the ideal humidity condition to store Dates for one year without any further degradation. In traditional open sunshine the huge quantity of Dates are dried in over 150 h hours and requires hectare of area to spread the Dates. Moreover, the quality of Dates in the open sunshine is affected badly due to two main reasons. Firstly, the heavy dust in the area that sticks the Dates during the drying process makes them unable to eat. Secondly, the Monsoon rains in the months of July and August also destroys Dates placed in the open areas for drying. Dera Ismail (D.I.) Khan, a remote district of Khyber Pakhtoon Khawa province of Pakistan, was selected to study the performance of Dates dryer, where solar insolation is 700-750 W/m2 in the months of July and August. The Dates were dried continuously and during off sunshine hours biomass auxiliary source was used. This solar dryer, containing eight trolleys and each trolley is loaded with twelve trays, is the first in Pakistan to dry a large amount of Dates. Moreover, the unglazed transpired dryer is designed in such a way that it can withstand the dusty atmosphere of D.I. Khan and also protect the Dates from dust and rainy water during the drying period. The design does not have any adverse effect on the quality of dried Dates. In D.I. Khan around 350 days are sunny per year and solar thermal technology is economically feasible compared to other conventional energy resources with a payback period of 3 and 7.5 years compared to un-subsided and subsided cost of Natural Gas respectively. The Natural Gas is the cheapest conventional energy source in Pakistan. But solar thermal technology is yet not popular source of energy in the area due to lack of information, fear of initial capital cost and weak government policies for renewable energies. This study also incorporates the recommendations to overcome these issues regarding Solar Thermal Technology, PACS Number: 44.40.+a, 89.30.Cc, 84.60.- h, 89.30.-g.